The role of the family in immigrants' labor-market Activity: An Evaluation of Alternative Explanations - Baker, Michael; Benjamin, Dwayne (American Economic Review, 1997)
The authors evaluate some explanations of immigrants' family labor-supply behavior. Upon arrival, immigrant husbands work less than natives but immigrant wives work more. A conventional labor-supply model uses wage assimilation to explain these differences but is not supported by the data. More favorable results are obtained for the 'family investment model, ' in which wives in immigrant families take on 'dead-end' jobs to finance their husbands' investments in human capital. The authors conclude that family composition is an important correlate of immigrants' assimilation and the family investment model can account for many of the patterns in the data. Copyright 1997 by American Economic Association.